PEMBELAJARAN PJOK DI SD GMIT MANULAI 2 SELAMA PANDEMI - I Nyoman Wahyu Esa Wijaya; Jurdan Martin Siahaan (Nusa Cendana University, 2022)
The covid-19 pandemic in the 2021/2022 school years learning from home is implemented GMIT Elementary school starting 2. Associated with pshycal education and health are indentical to movement learning.This study aims to determine the process and obstacles in the implementation of online learning experienced by student, parents and teacher of pshical education subjects, sport and health and leaarnig out come of fifth graders in the 2021/2022 scoolh year. The research is a qualitative descriptive with interview and documentation methods, The informants in this study were nineteen fift grade students, five parents of fitth grade students and teachers of physical education, sports and health. The results of the study concluded that the implementation of online learning in the school year at SD GMIT Manulai 2 Alak district kupang city Effective based on student learning outcomes, as well as the processes experienced by teacher, students and parents who focus on the same goal, namely the success of students in completing sport and health physical education learning in the 2021/2022 school year.